Getting the Message Across: Examining Malaysia’s Covid-19 Public Service Announcement (PSA) Infographics - Jerome, Collin; Ting, Su Hie; Podin, Yuwana (UNIMAS Publisher, 2021)
The current COVID-19 pandemic has become an unprecedented public health crisis and there is much ongoing research investigating its wide-ranging impacts on all areas of society and people's everyday lives. This article presents preliminary findings of an ongoing study that inquires into Malaysia's COVID-19 public service announcement (PSA) infographics and how they convey much-needed information to the general public during the pandemic period. Drawing upon research on infographics in healthcare and health risk communication, the article examines COVID-19 PSA infographics that have been produced in Malaysia and the ways they achieve what they are designed to do. The findings show that the infographics 1) are numerous and mostly presented in the informational and process-based types, 2) cover various topics related to the information on the novel virus, its risks, and recommended preventive and control measures, 3) possess key components of infographic and (4) adopt a three-way process of engaging the target audience. The findings also reveal several key points worth considering in thinking about the infographics, including whether they communicate the right message to the right audience at the right time and whether they are designed according to the principles of message design in health risk communication.